Training medical undergraduates in the core disciplines of community medicine through community postings – an experience from India. Issue 3 (1st July 2016) - Shewade, Hemant Deepak; Palanivel, Chinnakali; Jeyashree, Kathiresan
Abstract : Objective: Family medicine, epidemiology, health management and health promotion are the core disciplines of community medicine. In this paper, we discuss the development of a community posting program within the framework of community medicine core disciplines at a primary health centre attached to a teaching hospital in Puducherry, India. Methods: This is a process documentation of our experience. Results: There were some shortcomings which revolved around the central theme that postings were conducted with department in the teaching hospital as the focal point, not the primary health centre (PHC). To address the shortcomings, we made some changes in the existing community posting program in 2013. Student feedback aimed at Kirkpatrick level 1 (satisfaction) evaluation revealed that they appreciated the benefits of having the posting with PHC as the focal point. Feedback recommended some further changes in the community posting which could be addressed through complete administrative control of the primary health centre as urban health and training center of the teaching hospital; and also through practice of core disciplines of community medicine by faculty of community medicine. Conclusion: It is important to introduce the medical undergraduates to the core disciplines of community medicine early through community postings. Community postings should be conducted with primary health centre or urban health and training centre as the focal point.